Epistemic Injustice in Obstetrics and Gynecology - Sitian LIU (Yixue yu zhexue, 2025)
Epistemic injustice in the medical field is primarily manifested through the epistemic privilege of healthcare professionals, which leads to the underestimation of patients' epistemic credibility. This issue is particularly prominent in the field of obstetrics and gynecology. Doctors often overlook patients' experiences due to their epistemic advantage, resulting in patients sometimes enduring unfair treatment rooted in biases against their epistemic capabilities. Additionally, the application of artificial intelligence in medicine may exacerbate this problem because of inherent biases in the data and models. To reduce the occurrence of such cognitive injustice, the article proposes a phenomenological approach that emphasizes the importance of patients' first-person experiential data. It also advocates for the development of responsible artificial intelligence systems to help mitigate epistemic biases in obstetrics and gynecology, thereby not only improving medical outcomes but also fostering a more harmonious doctor-patient relationship.